Flow rectification and reversal mass flow in printed periodical microstructures - Osorio Nesme, Anuhar; Rauh, Cornelia; Delgado, Antonio (Engineering Applications of Computational Fluid Mechanics, 2012)
The present paper aims at the study of flow rectification, reversal mass transport and flow characterization occurring in two-dimensional channels with designed asymmetric microstructures periodically placed in the streamwise direction using the lattice Boltzmann method. The present contribution deals with microchannels containing nozzle-diffuser-like structures (grooves), which promote net flow in a preferential direction for flows with time-dependent alternating direction. Different geometries are analyzed by varying the halfangle φ which defines the groove. The influence of φ on the flow rate ratio Q net and on flow rectification efficiency ε is presented for low-to-moderate-Reynolds-number flows. It is shown that geometries with large angles exhibit poor flow rectification during the steady state regime. In general, for all geometries studied, the flow rectification occurs in the diffuser direction for subcritical flows (stationary flows) and in the nozzle direction for supercritical flows (self-sustained oscillatory flows). Grooves with φ =11.31° and φ. 26. 56° perform with the highest rectification efficiency but only at high driving body forces.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.flowre
Keywords: Flow rectification; Lattice Boltzmann method; Rectification efficiency; Reversal mass transport